Quality of outpatient nursing care: a scoping review - Bruna Noschang de Brum; Carlise Rigon Dalla Nora; Adriana Roese Ramos; Luciana Foppa; Deise Lisboa Riquinho (Revista Latino-Americana de Enfermagem)
Objective: to map national and international scientific literature on the quality of outpatient nursing care. Method: a scoping review guided by the Joanna Briggs Institute Collaboration, conducted across 12 databases and repositories. Only original articles evaluating the quality of outpatient nursing care were included. No restrictions were applied regarding time, methodology, or language. Data were mapped and organized through thematic and statistical descriptions of the articles. This review was registered on the Open Science Framework platform. Results: a total of 45 studies published between 1984 and 2021 were identified, resulting in 17 quality indicators for outpatient nursing care, grouped according to Donabedian’s triad: four for structure, seven for process, and six for outcomes. The predominant area of care was oncology. Among the analyzed studies, 55.3% focused on patients. The most frequently cited indicators were continuing health education, service organization, communication, care coordination, and the nursing process. Conclusion: the limited number of studies in this field, compared to other areas of nursing, highlights the underexploitation of the topic both nationally and internationally. Additionally, the diversity of identified indicators underscores the lack of standardization in these data.